Chłopiec z rozszczepem wargi i wyrostka zębodołowego z późno zdiagnozowaną hiperdoncją - opis przypadku = A boy with lip and alveolar bone cleft with late diagnosis of hiperdontia - case report - Osica, Piotr; Janas, Anna; Janeczek, Karolina (Journal of Education, Health and Sport, 2015)
Osica Piotr, Janas Anna, Janeczek Karolina. Chłopiec z rozszczepem wargi i wyrostka zębodołowego z późno zdiagnozowaną hiperdoncją - opis przypadku = A boy with lip and alveolar bone cleft with late diagnosis of hiperdontia - case report. Journal of Education, Health and Sport. 2015;5(4):135-142. ISSN 2391-8306. DOI: 10.5281/zenodo.16691 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A135-142 https://pbn.nauka.gov.pl/works/553745 http://dx.doi.org/10.5281/zenodo.16691 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.03.2015. Accepted: 27.03.2015. Chłopiec z rozszczepem wargi i wyrostka zębodołowego z późno zdiagnozowaną hiperdoncją - opis przypadku A boy with lip and alveolar bone cleft with late diagnosis of hiperdontia - case report Piotr Osica1, Anna Janas2, Karolina Janeczek1 1 Zakład Chirurgii Stomatologicznej Uniwersytetu Medycznego w Łodzi Kierownik: prof. zw. dr hab. n. med. Grażyna Grzesiak-Janas 2 Zakład Stomatologii Ogólnej Uniwersytetu Medycznego w Łodzi Kierownik: prof. dr hab. n. med. Jerzy Sokołowski Adres do korespondencji: Dr n. med. Piotr Osica Zakład Chirurgii Stomatologicznej UM w Łodzi 92 – 213 Łódź, ul. Pomorska 251 pioosica@interia.pl Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-01 Streszczenie W pracy przedstawiono przypadek 12 letniego chłopca z rozszczepem wargi i wyrostka zębodołowego z późną zdiagnozowaną hiperdoncją. Słowa kluczowe: hiperdoncja, rozszczep wargi, leczenie chirurgiczno-ortodontyczne. Summary The article describes a case of a 12 y.o boy with lip and alveolar bone cleft with late diagnosis of hiperdontia. Keywords: hiperdontia, cleft lip, treatment chirurgic-orthodontic.